An analysis and criticism of the arguments for the individuality of the hijab - Ã™Â…Ã™Â„Ã™Âƒ Ã˜Â§Ã™ÂÃ˜Â¶Ã™Â„Ã›ÂŒ Ã˜Â§Ã˜Â±Ã˜Â¯Ã™ÂƒÃ˜Â§Ã™Â†Ã›ÂŒ, Ã™Â…Ã˜ÂÃ˜Â³Ã™Â†; Ã™ÂÃ™Â„Ã˜Â§Ã˜Â, Ã™ÂÃ˜Â§Ã˜Â·Ã™Â…Ã™Â‡ (Ã™ÂÃ™Â‚Ã™Â‡ Ã™Âˆ Ã˜Â§Ã˜ÂµÃ™ÂˆÃ™Â„)
The hijÄb is a religious obligation based on numerous sources and jurisprudential arguments. Some consider the hijÄb as an individual and not a social issue, arguing that it essentially does not fall in the sphere of state interference and even other peopleâs intervention. The present paper discusses this important and critical issue within the responsibility domain of the Islamic state. Thus, by challenging the arguments of those who believe in the individuality of the hijÄb, the paper aims to prove its sociality. The arguments are divided into two major categories: the juridical-legal and the Qurâanic, each of which find their appropriate responses in this paper. In addition, the jurisprudential aspect is studied more deeply. It should be noted, however, that the social essence of the hijÄb and chastity, as well as the responsibility of the Islamic state as to protect and propagate the ideal, does not mean that the government should resort to force or judicial and penal measures for that purpose. Instead, on the basis of jurisprudential arguments, the state is obliged to adopt some of the best ways and mechanisms in order to encourage the people to exercise this good deed.